Legal Protection of Health for Occupational Safety in Siwalan Village, Gresik Regency - Yeni Vitrianingsih (Pusat Riset dan Inovasi Nasional, 2025)
Every citizen has the right to get a job. Meanwhile, the work that is necessary for people to live a decent life for humanity is a job that pays enough and does not cause accidents or diseases. Law on Health No. 17 of 2023 Law No. 1 of 1970 on Occupational Safety: This law is the legal basis for the implementation of K3LH in Indonesia. Law No. 13 of 2003: Article 88 paragraph (1) of this Law states that every worker has the right to protection for occupational safety and health. Permenaker No. 5 of 1996: This regulation regulates the K3 Management System. Meanwhile, getting enough wages in jobs in our country is very difficult and the weak protection of workers, especially regarding freelance daily workers, has not received much attention in the government's observation. Legal protection plays a crucial role in ensuring that K3 coaching runs effectively and sustainably. This includes regulations that require K3 training, the appointment of competent K3 officers, and incident reporting. The main challenges include ineffective supervision and low legal awareness. A robust legal framework, including K3 training, certification, and auditing standards, is essential to encourage investment in quality coaching. Strict law enforcement against K3 violations is also vital to minimize accidents and occupational diseases.